The Impact of Workcation Program, Digital Entrepreneurship, and Strengthening Local Wisdom on the Success of Sustainable Tourism in Bali - Hakim, Nur; Didik Widiarta , I Putu Gede; Bunyamin, Ilham Akbar (West Science Interdisciplinary Studies, 2025)
This study examines the impact of workcation programs, digital entrepreneurship, and local policy strengthening on the success of sustainable tourism in Bali, Indonesia. Utilizing a quantitative research approach, data was collected from a sample of 150 community members using a Likert scale (1-5). The analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3). The results reveal that workcation programs, digital entrepreneurship, and local policy strengthening all have significant positive effects on the success of sustainable tourism in Bali. Furthermore, workcation programs and local policy strengthening positively influence digital entrepreneurship, creating a synergistic effect. These findings highlight the importance of a multi-faceted approach to fostering sustainable tourism through the integration of workcation initiatives, digital business innovation, and supportive policies. The study provides valuable insights for policymakers and tourism stakeholders looking to enhance sustainable tourism practices in Bali.